POPULASI HAMA Spodoptera exempta PADA TANAMAN PADI SAWAH DI DESA MOLOMPAR DUA UTARA KABUPATEN MINAHASA TENGGARA - Vinolia P. Tompunu; Mareyke Moningka; Redsway Maramis; Daisy Kandowangko (COCOS, 2014)
ABSTRACKRice is the main commodity for the Indonesian people, because rice is an important food crop in which half of Indonesia's population depend on rice, even half of the world's population makes rice as the staple food. This study aims to determine the population of S. exempta pests in rice paddy fields in the village of Two Molompar Northern District of East Tombatu Southeast Minahasa regency. The research was conducted at the location of paddy rice cultivation In October-December 2013 This study used a survey method with sampling deliberately by choosing plant pests. Materials and tools used in this research is cropping Rice, meter, Aqua Glass, Peg, paper labels, plastic rope, Scissors, Box collection, Microscope, Petridis, Calculators, digital camera for documentation and stationery. The observation of the larval population of S. exempta in rice paddy fields in the village molompar two north, found that populations of this pest on plant age 60 HST is 3.3 tails. Then the next observation at the age of 67 plants as much as 2.1 HST observations of the tails and the third at the age of 75 plants of S. exempta HST population is 2 larvae.